Oxygeranylated Coumarins from The Root of Limonia accidisima L. and Their DPPH Radical Scavenging Activity - Tjahjandarie, Tjitjik Srie (Scholars Research Library, 2016)
Four oxygeranylated coumarins namely as auraptene (1), 6-methoxy-auraptene (2), 7-(2’E,5’E)-7’-hydroxy-3’,7’- dimethylocta-2’,5’-dienyloxy) coumarin (3) and 7-((2’E,6’E)-5’-hydroxy-3’,7’-dimethylocta-2’,6’-dienyloxy) coumarin (4) were isolated from the roots of Limonia accidissima L. Their structures were determined based on UV, IR, HRESIMS, 1D and 2D NMR analysis.. The ethyl acetate extract as well as compounds 1-4 were evaluated for their antioxidant activity against DPPH radical scavenging. Compound 3 showed very high activity against DPPH radical